2021
DOI: 10.3390/ijerph18094626
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Back-Squat Performance at Submaximal Loads: Is the Reliability Affected by the Variable, Exercise Technique, or Repetition Criterion?

Abstract: This study aimed to compare the between-session reliability of different performance variables during 2 variants of the Smith machine back-squat exercise. Twenty-six male wrestlers performed 5 testing sessions (a 1-repetition maximum [1RM] session, and 4 experimental sessions [2 with the pause and 2 with the rebound technique]). Each experimental session consisted of performing 3 repetitions against 5 loads (45–55–65–75–85% of the 1RM). Mean velocity (MV), mean power (MP), peak velocity (PV), and peak power (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(113 reference statements)
2
1
0
Order By: Relevance
“…Although this study provides novel information about the accuracy of %Rep-%VL relationships for prescribing the resistance training volume, several limitations and potential areas for future research are important to be considered. First, although it was comparable with previous studies (18,24), the fact of including a relatively small sample size of male sports science students may limit the generalizability of the current findings. For example, it is well documented that experienced lifters have an enhanced ability to recruit high-threshold motor units when compared with novice lifters (31).…”
Section: Discussionsupporting
confidence: 70%
“…Although this study provides novel information about the accuracy of %Rep-%VL relationships for prescribing the resistance training volume, several limitations and potential areas for future research are important to be considered. First, although it was comparable with previous studies (18,24), the fact of including a relatively small sample size of male sports science students may limit the generalizability of the current findings. For example, it is well documented that experienced lifters have an enhanced ability to recruit high-threshold motor units when compared with novice lifters (31).…”
Section: Discussionsupporting
confidence: 70%
“…Our main hypothesis was that the protocol consisting of performing three sets of 30 repetitions of squats at 50% of 1RM has a higher test-retest reliability than three sets of 12 repetitions of squats at 75% of 1RM. This hypothesis is in line with the results obtained by Çetin et al [27], which demonstrated that performing an exercise with loads between 60-80% 1RM resulted in a higher inter-session CV as well as a higher mean difference; and by Pérez-Castilla et al [28] which indicated that, with loads around 85% 1RM, the CV increases as the load decreases.…”
Section: Introductionsupporting
confidence: 90%
“…The parallel back-squat was consistently executed on a Smith machine (Technogym, Gambettola, Italy). Starting from a standing position with feet shoulder-width apart and the barbell positioned high on the back near the acromion, participants would squat until their thighs were parallel to the ground and then ascend as quickly as possible [22]. Constant downward pressure was maintained on the barbell throughout the movement, and jumping was prohibited.…”
Section: Procedures 231 Rm Evaluation and Familiarization (Sessions 1-3)mentioning
confidence: 99%